Harnessing an invasive species’ waste for syngas production: Fast pyrolysis of rosehip seeds in a bubbling fluidized bed - Torres Sciancalepore, Rodrigo Agustin (2025)
This study examines the fast pyrolysis of rosehip seed waste (RSW) in a fluidized bed reactor, evaluating its potential for syngas production and effective waste valorization. The fluidization behavior of sand/RSW mixtures was characterized by determining the minimum fluidization velocity (Umf) from pressure drop measurements. Umf increased with RSW content, ranging from 0.227 to 0.257 m/s. Fluid-dynamic tests conducted in an acrylic prototype assessed bed expansion and mixing, showing stable fluidization at 10% RSW concentration without axial slugging. The bed expanded to 68% above the fixed-bed height, while bubble formation promoted uniform mixing and prevented solid segregation. Pyrolysis experiments were performed in a steel reactor using a nitrogen flow three times the Umf, an initial bed height of 2.5 cm, and a 10% RSW mixture. The reactor operated between 400 and 600 ◦C, and syngas composition was analyzed. At 600 ◦C, carbon monoxide and hydrogen yields reached 13.868 mmol/gRSW and 7.914 mmol/gRSW, respectively—values notably higher than those obtained under slow pyrolysis conditions. These findings demonstrate that high-efficiency fluidized bed technology provides a sustainable pathway to convert invasive biomass into clean syngas, integrating waste mitigation with renewable energy generation.